Explorando a versatilidade dos fosfetos de níquel na redução eletroquímica de moléculas de interesse energético e ambiental - Silva, Anelisse Brunca da (Universidade Federal de São Carlos, 2024)
This study investigates how the surface and bulk engineering of Ni−P catalysts, synthesized via electrodeposition, can optimize selectivity in the electroreduction reactions of H₂O/H⁺, NO3⁻, and the co-reduction of NO₃⁻ and CO₂. The influence of the Ni molar ratio in the deposition bath was analyzed to enhance the catalytic properties of nickel phosphide supported on Ni foam for the Hydrogen Evolution Reaction (HER). The optimal Ni concentration resulted in electrodes with low overpotentials and high durability across different pH ranges, reaching 69, 165, and 56 mV at –10 mA cm⁻2 in alkaline, neutral, and acidic media, respectively. This performance was attributed to the granular structure, large surface area, and amorphous nature of the electrode—factors that favor interaction with the electrolyte and improve the HER kinetics, leading to a Tafel slope of 71 mV dec⁻1. XPS analyses confirmed the stability of the Ni−P bond, and the minimal potential variation observed in stability measurements demonstrated the robustness of the catalyst in neutral and alkaline electrolytes. To enable its application in the nitrate reduction reaction, the nickel phosphide film was deposited on carbon paper and functionalized with δ-FeOOH nanoplates. This modification led to the formation of CP/Ni−P/δ-FeOOH heterostructures, which exhibited high efficiency in nitrate-to-ammonia conversion, suppressing HER and promoting NO3⁻ adsorption. The heterostructure achieved a Faradaic efficiency of 98% ± 0.72 at -0.3 V vs. RHE, with an NH₃ production rate of 8.49 mg h⁻1 cm⁻2. Stability was maintained over 12 consecutive cycles, even with the use of a green, non-toxic binder, preserving the surface modification. δ-FeOOH stabilized intermediates through hydrogen bonding with -OH groups in its structure, controlling the formation of Hads and promoting the selective hydrogenation of NO₃⁻ intermediates. Simultaneously, the incorporation of tin (Sn) into nickel phosphide proved to be a strategic approach for the co-reduction of CO2 and NO3⁻, redirecting selectivity toward carbon monoxide production while suppressing competitive HER. The addition of Sn led to the formation of deposits composed of cubic nanoparticles of nickel and tin phosphides, also favoring urea synthesis, with a Faradaic efficiency of up to 62%. The synergy between Sn and Ni active sites enabled the simultaneous activation of CO2 and NO3⁻, facilitating intermediate coupling. This study highlights the great potential of modified nickel phosphides for catalytic applications, contributing to the sustainable production of high-value-added products such as urea, ammonia, and H2 from abundant molecules.
Exploring the versatility of nickel phosphides in the electrochemical reduction of molecules of energy and environmental interest T
Keywords: Fosfeto de níquel; Reação de desprendimento de hidrogênio; Redução eletroquímica de nitrato; Redução simultânea de nitrato e dióxido de carbono; CIENCIAS EXATAS E DA TERRA::QUIMICA